Gravity Interpretations to Investigate the Deep Geological and Structural Status of Middle Atlas Chain Region, Morocco - Youssef Ouahzizi; Driss El Azzab; Mohamed Charroud; Mohammed Tazi; Abdelkhiar Ali (Iraqi Geological Journal, 2023)
The Moroccan Middle Atlas is an intracontinental chain characterized by a combination of tectonic, sedimentary, and magmatic events. These events influenced the Middle Atlas basement structure and its morphology. In order to improve our understanding of the subsurface and deep geological structures, a gravimetric investigation was carried out. A residual gravity map and its horizontal derivative were computed and interpreted. We present in this work the main findings: The residual gravity anomaly map shows fourteen positive anomalies which are well correlated with the undulated Paleozoic basement in the Middle Atlas or with the High Moulouya and the Merhraoua Anticlinorium in the Northeastern part of the Middle Atlas chain.It also exhibits sub-circular negative anomalies related to the thick subsurface Meso-Cenozoic cover of the Middle Atlas chain depocenters located in the center and southeastern parts of this chain. These anomalies are correlated with the Bou Anguer, Bekrit, Tazouta, Enjil, and Almis Mermoucha basins; the Bounacer mount; and the extension of Boumia granite in the High Moulouya. The horizontal gravity gradient map discloses that the study area is mainly affected by the NE-SW trends as major faults, while the N-S, NW-SE, and E-W are minor faults. They’re superposed with the Southern Middle Atlas Accident, the North Middle Atlas Accident the Tizi N’tretten Accident, and their branches. They are due to the alpine neotectonic reactivation phases of the Paleozoic and Jurassic heritaged faults. A synthetic structural map displaying the lateral extension of most Middle Atlas faults was postulated. Consideration is also being given to explore the buried faults or unmapped ones. Our final map represents an efficient and effective tool to help decision-makers during mining exploration.